When Stories Go Wrong. (January 2014) - Lindemann, Hilde
Abstract Stories do many different kinds of moral work. Because they can depict time passing, feature certain details while downplaying others, draw connections among their internal elements, display causal relationships, and connect themselves to other stories, they are particularly well suited to the task of modeling a puzzling clinical situation. A story maps the situation's contours, picking out the details that, together, constitute the moral reasons for doing what may or must be done. When moral deliberators construct a story, they come to understand the situation in a certain way, and that, in turn, guides their sense of how they should act in or with respect to it. But stories don't just represent situations‐they can also misrepresent them. For that reason, if we are to use stories as guides to action, we have to be sure we get them right. In what follows I offer three clinical situations that are either about to be or have already been narratively misrepresented. I'll explain how the stories go wrong, point out the undesirable consequences of acting on them, and offer alternative ways of depicting the situations that could bring them to a morally successful resolution.